2004
DOI: 10.1097/00001756-200403010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation changes associated with motor recovery in patients with precentral knob infarct

Abstract: We investigated the cortical activation changes associated with motor recovery in six hemiparetic patients with precentral knob infarct. fMRI at 1.5 T with finger movements at a fixed rate was performed twice in each patient, 1 and 6 months after stroke onset. From the images obtained, the LI (laterality index) for the primary sensorimotor cortex (SM1) was calculated to measure the degree of the cortical activity concentration in the contralateral hemisphere. Our results showed that a greater improvement in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…7 The present data combined with the previous findings [2][3][4][5][6] suggest that ipsilateral motor tract is accountable, in part, for the mechanism of such an altered bihemispheric activation in the early stage of locomotor recovery. The enhanced SM1 activation in the affected hemisphere may be one common mechanism underlying motor recovery after stroke.…”
Section: Results Locomotor Function Datasupporting
confidence: 78%
See 2 more Smart Citations
“…7 The present data combined with the previous findings [2][3][4][5][6] suggest that ipsilateral motor tract is accountable, in part, for the mechanism of such an altered bihemispheric activation in the early stage of locomotor recovery. The enhanced SM1 activation in the affected hemisphere may be one common mechanism underlying motor recovery after stroke.…”
Section: Results Locomotor Function Datasupporting
confidence: 78%
“…1 In addition, several studies have been reported that cortical activities can change as motor recovery progresses in stroke patients. [2][3][4][5][6] The clarification of such a relationship is important because results of such studies could guide new rehabilitation strategies for stroke patients. The majority of these studies focused on the interval changes with the motor recovery of upper extremity, and little is known about the cortical activation changes concurrent with locomotor recovery in stroke patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the S1, the second largest source of CST fibers, which has DTI characteristics that are similar to those of the M1, appear to have an association with the high incidence of reorganization into the S1 following M1 infarct in patients with stroke. 10,[33][34][35] Several previous studies have reported the distribution of the CST origin in the cerebral cortex in primates. 11,12,14,17 In 1961,…”
Section: Discussionmentioning
confidence: 99%
“…As recovery progresses, a return to physiological activity can in part be documented [94]. The latter pattern, however, holds true only in patients with ‘good’ reconvalescence [105], highlighting the necessity for more comprehensive motor control in the case of severely affected innervation.…”
Section: Phase Of Consolidation and The Chronic Phasementioning
confidence: 99%